Impact of urbanization and landscape changes on the vegetation of coastal dunes along the Gulf of Mexico. Issue 2 (3rd April 2022) - Salgado, Karla; Martínez, M. Luisa; Álvarez-Molina, L. Lucero; Hesp, Patrick; Equihua, Miguel; Mariño-Tapia, Ismael
ABSTRACT: In Mexico, as in other countries, coastal urbanization and landscape changes are occurring at an unprecedented scale and rate, with potential negative impacts on local biodiversity. Nevertheless, studies of the impacts that such changes have on coastal dune vegetation are relatively scarce. In this study, we examined (a) the trends of urban sprawl and landscape changes along the coast of Veracruz for more than 20 years; (b) the impact of urban sprawl on plant species richness and plant functional groups; c) how landscape changes have affected plant diversity and community structure. Our results show an increasing urbanization along the coasts of the Gulf of Mexico, occurring at different rates, and being higher in locations closest to tourist areas. Plant species richness decreased with urban expansion while the proportion of plant functional types was altered. Inland species not tolerant to the beach-dune environment became more abundant in the most urbanized locations while the abundance of psammophytes decreased. Community structure (the dominant species) was modified with landscape changes. Our results are useful for an adaptive management strategy and will help develop sustainable beach management plans that should include the conservation of native and highly specialized species, such as psammophytes.